2006
DOI: 10.1056/nejmoa066224
|View full text |Cite|
|
Sign up to set email alerts
|

Glycemic Durability of Rosiglitazone, Metformin, or Glyburide Monotherapy

Abstract: The potential risks and benefits, the profile of adverse events, and the costs of these three drugs should all be considered to help inform the choice of pharmacotherapy for patients with type 2 diabetes. (ClinicalTrials.gov number, NCT00279045 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

76
2,134
19
93

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,726 publications
(2,322 citation statements)
references
References 32 publications
76
2,134
19
93
Order By: Relevance
“…Most of the recently published data have indicated that thiazolidinediones-associated fractures are restricted to the upper limb (forearm, hand and wrist) or distal lower limb (foot, ankle, fibula and tibia) [11]. Our study investigated the association between thiazolidinediones use and different fracture sites.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the recently published data have indicated that thiazolidinediones-associated fractures are restricted to the upper limb (forearm, hand and wrist) or distal lower limb (foot, ankle, fibula and tibia) [11]. Our study investigated the association between thiazolidinediones use and different fracture sites.…”
Section: Discussionmentioning
confidence: 98%
“…Since 2004, preclinical [3][4][5][6][7] and clinical studies [8][9][10] have indicated that thiazolidinediones use could alter bone metabolism, resulting in reduced osteoblastic bone formation and accelerated bone loss. As suggested by recent evidence from an epidemiological study [9] and a clinical trial [11], thiazolidinediones use is associated with a decrease in bone density in postmenopausal women. Similar findings have been reported in older men with type 2 diabetes [8].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…If the hypothesis that hypersecretion contributes to the progressive destruction of the beta cell is correct, it would have major implications for how type 2 diabetes should be treated. Perhaps the most compelling results suggesting a need for a change in practice have come from the a Diabetes Outcome Progression Trial (ADOPT) [49]. In this study, the clinical endpoint was failure of monotherapy drug treatment as reflected by a fasting plasma glucose level of greater than 10 mmol/l in newly diagnosed patients with type 2 diabetes.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…4,32 In type 2 diabetics, thiazolidinedione improved glucose control despite significant weight gain. 33 Importantly, fat incretion occurred mostly in peripheral subcutaneous adipose tissue, often in the absence of any changes in visceral mass, resulting in a more favorable PFM/CFM ratio. [34][35][36][37] Redistribution of fat mass from peripheral locations to abdominal depots following a carbohydrate-enriched diet also led to diminished insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%